Probable toxin producer responsible for the first occurrence of paralytic shellfish poisoning on the east coast of Peninsula malaysia - Usup, G.; Pin, L.C; Teen, LP; Asmat, Ahmad (Malays. Appl. Biol., 2002)
A study was carried out to determine the presence of potentially toxic dinoﬂagellate species in the Sungai Geting coastal lagoon in Ttnnpat, Kelantan. This followed the occurrence of paralytic shellﬁsh poisoning (PSP) in the area in September 2OO1. Only 12 dinollagellate species were found in net plankton samples collected from the lagoon during the week of the event. Of these, four were potentially toxic, namely Dinophysis caudata, D. rorundata, D. miles, and Alexandrium minutum. Among these species only A. ...